The Role of Hope and Conservation Attitudes in Current Conservation Action and Future Conservation Intention: Implications for Community-Led Conservation in Aotearoa New Zealand - Ough Dealy, Helen (Auckland University of Technology, 2023)
Introduced mammalian predators threaten Aotearoa New Zealand’s endemic species with extinction. Current Aotearoa New Zealand voluntary community-led conservation (CLC) actions (e.g., planting, weeding, predator control) support present and future biodiversity restoration. CLC predator control efforts, in particular, may contribute to a predator-free nation by 2050. However, while present-day conservation volunteer efforts are measurable, future CLC activity is uncertain. Aotearoa New Zealand national open-source demographic data and national and regional conservation attitude and action data projections suggest an ageing, more diverse population with changing urban/rural population ratios. Increased financial debt extending to later ages implies an extended time in employment and work insecurity for some. These factors may reduce future active regular conservation volunteering, thus limiting CLC group sustainability and Aotearoa New Zealand’s current predator control achievements and future predator-free aspirations. Therefore, understanding factors that positively influence CLC volunteers to undertake conservation action now and in the future may support conservation volunteer retention, recruitment, and thus biodiversity restoration. CLC efforts rely on individual willpower and problem-solving to achieve future-oriented goals. Snyder’s Theory of Hope incorporates agency and pathways thinking, thus supporting current conservation action and future conservation intention. Likewise, understanding conservation attitudes may support voluntary CLC engagement. In this thesis, I adopt a mixed-method approach that identifies and addresses a gap in CLC recruitment and retention, the potential relationships between hope, conservation attitudes, current conservation action, and future conservation intention. First, I develop and administer collage-elicited interviews, an innovative visual arts-based means of better understanding people’s feelings about and place in their present and future worlds. I then conduct a reflexive thematic analysis of these interviews resulting in six common themes, commitment to the natural world, connectivity to the environment and other people, group action, learning cycle, practical solutions, and unconditional belief. Second, I survey 243 Aotearoa New Zealand adults’ hope, conservation attitudes (derived from the six collage-elicited themes), current conservation actions, and future conservation intentions. Survey results indicated a complex relationship between conservation attitudes, hope, current conservation action, and future conservation intention in the adult Aotearoa New Zealand context. Understanding Aotearoa New Zealand adult conservation attitudes may help increase conservation efforts and support sustainable CLC project designs, delivering positive outcomes for biodiversity in the long term. Furthermore, my research addresses the conservation attitude and hope knowledge-action gap by proposing practical approaches to current conservation volunteer retention and future intention to act for conservation. These include developing an Accessing and Applying Conservation Attitudes kit enabling CLC groups, conservation-related government departments and NGOs to support current CLC biodiversity restoration actions and future intentions.